Unsaturated soil properties of a high compacted fill with settlement monitoring system. (December 2022) - Ameen, Aynoor; Özener, Pelin
Abstract: Compacted soil has a wide range of applications, including earth dams, earthwork, airport runways, highways, and more. High fills and embankments necessitate an in-depth examination of the short and long-term circumstances of embankment settling. High compacted fills and unsaturated soils are explored, with numerous factors influencing soil suction taken into account. In this way, we propose a study that uses statistics to assess unsaturated soil parameters for a highly compacted fill. The findings of the proposed study indicate that water content, saturation degree, clay fractions, liquid limit, plasticity index, compression index, pre-consolidation pressure, and cohesion are all vital factors in determining the matric suction of compacted soils. The proposed study emphasizes the significance of assessing the connections and correlations between soil suction and these parameters.